Magnetic and Fluorescent Dual-Labeled Genetically Encoded Targeted Nanoparticles for Malignant Glioma Cell Tracking and Drug Delivery - Anna N. Gabashvili; Nelly S. Chmelyuk; Vera V. Oda; Maria K. Leonova; Viktoria A. Sarkisova; Polina A. Lazareva; Alevtina S. Semkina; Nikolai A. Belyakov; Timur R. Nizamov; Petr I. Nikitin (MDPI AG, 2023)
Human glioblastoma multiforme (GBM) is a primary malignant brain tumor, a radically incurable disease characterized by rapid growth resistance to classical therapies, with a median patient survival of about 15 months. For decades, a plethora of approaches have been developed to make GBM therapy more precise and improve the diagnosis of this pathology. Targeted delivery mediated by the use of various molecules (monoclonal antibodies, ligands to overexpressed tumor receptors) is one of the promising methods to achieve this goal. Here we present a novel genetically encoded nanoscale dual-labeled system based on Quasibacillus thermotolerans (Qt) encapsulins exploiting biologically inspired designs with iron-containing nanoparticles as a cargo, conjugated with human fluorescent labeled transferrin (Tf) acting as a vector. It is known that the expression of transferrin receptors (TfR) in glioma cells is significantly higher compared to non-tumor cells, which enables the targeting of the resulting nanocarrier. The selectivity of binding of the obtained nanosystem to glioma cells was studied by qualitative and quantitative assessment of the accumulation of intracellular iron, as well as by magnetic particle quantification method and laser scanning confocal microscopy. Used approaches unambiguously demonstrated that transferrin-conjugated encapsulins were captured by glioma cells much more efficiently than by benign cells. The resulting bioinspired nanoplatform can be supplemented with a chemotherapeutic drug or genotherapeutic agent and used for targeted delivery of a therapeutic agent to malignant glioma cells. Additionally, the observed cell-assisted biosynthesis of magnetic nanoparticles could be an attractive way to achieve a narrow size distribution of particles for various applications.